Expression and Characterization of a New PolyG-Specific Alginate Lyase From Marine Bacterium Microbulbifer sp. Q7 - Yang, Min; Yu, Yuan; Yang, Suxiao; Shi, Xiaohui; Mou, Haijin; Li, Li (Frontiers in Microbiology, 2018)
Alginate lyases play an important role in preparation of alginate oligosaccharides. Although a large number of alginate lyases have been characterized, reports on directional preparation of alginate oligosaccharides by alginate lyases are still rather less. Here, a gene alyM encoding a new alginate lyase AlyM was cloned from Microbulbifer sp. Q7 and expressed in Escherichia coli. AlyM exhibited the maximum activity at pH 7.0 and 55°C and showed special preference to poly-guluronic acid (polyG). Glycine promoted the extracellular secretion of AlyM by 3.6 times. PBS and glycerol significantly improved the thermal stability of AlyM, the enzyme activity remained 75% and 78% after heat-treatment at 45℃ for 2 h, respectively. ESI-MS analysis suggested that AlyM mainly produced oligosaccharides with degrees of polymerization (DP) of 2-5. The results of 1H-NMR showed that guluronic acid (G) occupied the reducing end of the end products, indicating that AlyM preferred to degrade the glycosidic bond at the G-X linkage. HPLC analysis showed that the hydrolysis products with a lower degree of polymerization contained more G. Therefore, AlyM shows good potential to produce alginate oligosaccharides with specific M/G ratio and molecular weights.